1988
DOI: 10.1080/00049538808259070
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a 21-item version of the hopkins symptom checklist with New Zealand and united states respondents

Abstract: The Hopkins Symptom Checklist (HSCL) is a widely used measure of symptom distress and in particular is a valuable criterion measure in psychotherapeutic drug trials. Its reliability, validity, and sensitivity to change have been well established. However, its factor structure has been subject to much debate. In previous studies a wide range of different factor structum have been found by various researchers. The aim of the present study was to produce a short, less arduous, but acceptably reliable version of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 16 publications
(2 reference statements)
3
157
0
Order By: Relevance
“…The former were similar to those found in prior prison studies (e.g. Deane et al, 1999, M = 39.48), higher than university students (M = 34.08, Deane and Chamberlain, 1994) and a female nursing sample (M = 35.58, Green et al, 1988) but lower than a psychiatric outpatient sample (M = 44.32, Deane et al, 1992). The SIQ-4 (Reynolds, 1988;Pinto et al, 1997) was positively skewed.…”
Section: Help-seeking Variables and Distresssupporting
confidence: 87%
See 1 more Smart Citation
“…The former were similar to those found in prior prison studies (e.g. Deane et al, 1999, M = 39.48), higher than university students (M = 34.08, Deane and Chamberlain, 1994) and a female nursing sample (M = 35.58, Green et al, 1988) but lower than a psychiatric outpatient sample (M = 44.32, Deane et al, 1992). The SIQ-4 (Reynolds, 1988;Pinto et al, 1997) was positively skewed.…”
Section: Help-seeking Variables and Distresssupporting
confidence: 87%
“…The Hopkins Symptom Checklist-21 (HSCL-21, Green et al, 1988) is a 21-item version of the Hopkins Symptom Checklist (Derogatis et al, 1974) and assesses current emotional distress. Respondents rate each item (e.g.…”
Section: Considering the Time And Expense Involved In Counselling Itmentioning
confidence: 99%
“…Green, Walkey, McCormick, and Taylor (1988) developed a 21-item version of the original 58-item Hopkins Symptom Checklist (HSC) that measures psychological distress (Derogatis, Lipman, Rickels, Uhlenhuth, & Covi, 1974). Respondents rate how severely they have experienced each of the symptoms during the past 7 days, using a scale of 1 (notat all) to 4 (extreme(y).…”
Section: A T T I T U D E S Towardmentioning
confidence: 99%
“…The 21 -item version has been reported to have psychometric properties equivalent to the orignal version. Green et al (1988) reported the corrected split-half reliability of .91 and the alpha coefficient of .90 for the abbreviated version. The instrument has been found to have equivalent validity with European American, &can American, and Latino college students through confirmatory factor analysis (Cepeda-Benito & Gleaves, 2000).…”
Section: A T T I T U D E S Towardmentioning
confidence: 99%
“…According to Deane, Leathem, & Spicer (1992), the HSCL-21 has been shown to be related to counseling outcome measures and can detect changes across therapy. Green et al (1988), indicated the full scale HSCL-21 has a high level of internal consistency with a split-half reliability coefficient of .91 and an internal consistency alpha of .90. The current sample's internal consistency coefficient alpha was .92.…”
Section: Attitudes Towards Seeking Professional Psychological Help Tmentioning
confidence: 99%